Conceptual framework and research methods - Birner, Regina; Gupta, Surupa; Sharma, Neeru (International Food Policy Research Institute, 2011)
As shown by the literature review presented in Chapter 2, a variety of explanations have been offered as to why efforts to reform fertilizer and electricity supply to agriculture have not been successful, in spite of the obvious need for reform. Even so, major knowledge gaps remain, because different authors have focused on different explanatory factors-and, in the case of electricity, because the conditions vary considerably between states. Since most policy recommendations derived from the studies quoted above are generic, few strategies have been proposed for identifying the most relevant political obstacles to reform or devising specific reform strategies. To address this knowledge gap, the present study uses a conceptual framework (Figure 3.1) that makes it possible to consider multiple factors simultaneously.